Immune Checkpoint Inhibitors and Cardiac Toxicity: An Emerging Issue - Varricchi, Gilda; Marone, Giancarlo; Mercurio, Valentina; Galdiero, Maria R.; Bonaduce, Domenico; Tocchetti, Carlo G. (Current Medicinal Chemistry, 2018)
Although survival of patients with different types of cancer has improved, cardiotoxicity induced by anti-neoplastic drugs remains a critical issue. Cardiac dysfunction after treatment with anthracyclines has historically been a major problem. However, also targeted therapies and biological molecules can induce reversible and irreversible cardiac dysfunction. Over the last years, cancer immunotherapies haverevolutionized the clinical management of a wide spectrum of solid and hematopoietic malignancies previously endowed with poor prognosis. Immune checkpoint inhibitors are at the forefront of immunotherapy: the two most prominent are the targeting of cytotoxic-T-lymphocyte-associated antigen 4 (CTLA- 4) and of programmed cell death 1 (PD-1) and its ligand PD-L1. Ipilimumab (anti-CTLA-4) is the godfather of checkpoint inhibitors, whereas several blocking monoclonal antibodies targeting PD-1 (nivolumab and pembrolizumab) and PD-L1 (atezolizumab, durvalumab, avelumab, and BMS-946559) have been developed. Inhibitors of CTLA-4 and PD-1/PD-L1 pathway can unleash anti-tumor immunity and mediate cancer regressions. Although CTLA-4 inhibitors and PD-1 and PD-L1 blocking agents are frequently associated with a wide spectrum of immune-related adverse events, cardiac toxicity has been underestimated. However, early animal studies have demonstrated that after CTLA-4 inhibition and PD-1 deletion autoimmune myocarditis can occur. Moreover, PD-1 and PD-L1 can be expressed in rodent and human cardiomyocytes. During the last years several cases of fatal heart failure have been documented in melanoma patients treated with checkpoint inhibitors. The recent experience with cardiovascular toxic effects associated with checkpoint inhibitors introduces important concepts biologically and clinically relevant for future oncology trials and clinical practice.
Keywords: melanoma